EVALUASI POTENSI HASIL GALUR PADI LOKAL ACEH HASIL MUTASI RADIASI YANG TERINFEKSI BAKTERI Xanthomonas oryzae pv oryzae (Xoo) PENYEBAB PENYAKIT HAWAR DAUN BAKTERI - Lukman Hakim; Efendi Efendi; Marlina Marlina (Jurnal Media Pertanian, 2022)
Bacterial leaf blight caused by Xanthomonas oryzaepv. oryzae is a biotic stress that can reduce rice productivity. This study aimed to influence the effect of Xanthomonas oryzaepv. oryzae on yield and yield components of several strains of radiation mutated of Aceh's local rice. This study used a non-factorial randomized block design with 3 replications. The factors being tested are 18 strains seeds of the radiation mutated of Aceh's local rice. The results showed that Line 118-(Snbr-238-112-118-180-11) infected with Xanthomonas oryzaepvoryzae (Xoo) had the highest yield potential of 12.43 tons ha. -1. There was no effect of Xanthomonas oryzaepvoryzaebacterial infection on the yield components except for the number of tillers. The strains that showed moderate resistance to Xoo were Sisambay (USK-Snbr-M04-238-081-002), Sanberasi (USK-Snbr-M04-238-017-023), Siteluk (USK-Snbr -M04-238-092-097, Sulutan Unsrat-1, Sibabus (USK-Snbr-M04-238-110-116), Simuara (USK-Snbr-M04-238-091-097B), Sikuala (USK-Snbr - M04-238-114-120), IRBB, 118-(Snbr-238-112-118-180-11), 119- (Snbr-238-112-119-160-10), while the Simeulu strain (USK-Snbr -M04-238-074-001), Sibahak (USK-Snbr-M04-238-073-079), Siluan (USK-Snbr-M04-238-058-064), UF5, Sibuluh (USK-Snbr-M04- 238-V1B-017), Sialavan (USK-Snbr-M04-238-051-057E), Snb, and UF 1 showed a slightly susceptible reaction. Keywords : rice, leaf blight, yield potential